Factors affecting attitudes towards end-of-life care among medical students in China: a cross-sectional study - Jia, Rui; Chen, Min; Wang, Kang; Zhou, Xinrui; Wang, Xin; Yin, Jianhao; Duan, Peng; Gao, Ye (Technium Social Sciences Journal, 2021)
End-of-life care is regarded as a special kind of palliative care service. At present, people in our country are still relatively unfamiliar with end-of-life care. As a future medical worker whose work is about human life, health, disease, and death, their attitudes towards end-of-life of medical students affects all aspects of their medical behavior. The purpose of our research is to identify and describe factors associated with medical students' attitudes towards end-of-life care. Ninety-one medical students chosen by stratified random sampling at School of Medicine, Xi'an Jiaotong University completed several questionnaires focused on attitudes towards end-of-life care. The scores of end-of-life care attitudes of nursing major (133.3±9.6) is higher than clinical; grade 1 (132.3±9.8) is higher than grade 2, 3 or 4; "Calm and open atmosphere" in discussing the death situation at home (132.4±9.8) was higher than "never discussed death" and other situations; who had never suffered from serious illness (131.8±9.5) was higher than that of those who had suffered. The differences were statistically significant (P<0.05). The correlations coefficient between meaning of life (r=0.47), between the death fear dimension (r=-0.35), death escape dimension (r=-0.27), natural acceptance dimension (r=0.34), approach acceptance dimension (r=-0.21), escape acceptance dimension (r=-0.24), adolescent life events (r=0.19) and end-of-life care attitudes were significant correlation (P<0.01). After controlling of demographic sociological variables, psychological factors have made new contributions to hospice care attitudes, and the explained variance has increased by 32.0%. Medical students with different characteristics have significant differences in end-of-life care attitudes, which suggesting the lack of education in end-of-life care in our country, and the failure of education to enable medical students of different backgrounds to establish a scientific, rational and humanistic care attitude.